Thysanoptera host-plant associations, with an account of species living on Tamarix, and a new species of Lissothrips (Phlaeothripidae) - Minaei, Kambiz; Mound, Laurence (Zootaxa, 2020)
Eight unrelated Thysanoptera species are known to be associated with the arid zone plant genus Tamarix [Tamaricaceae]. One new species, Lissothrips hemingi sp.n., is described from Iran based on specimens collected on branches of Tamarix. Liothrips jazykovi Moulton, described from specimens taken on Tamarix, is considered a new synonym of Liothrips reuteri (Bagnall), a widespread species on the foliage of this plant.